2021
DOI: 10.1111/disa.12463
|View full text |Cite
|
Sign up to set email alerts
|

Evidence summary of water, sanitation, and hygiene (WASH) coordination in humanitarian response

Abstract: Providing water, sanitation, and hygiene (WASH) to emergency-affected populations is necessary for reasons of dignity and disease control. Such a (humanitarian) response is coordinated via the 'cluster approach'. This study utilises a literature review, an appraisal of and analysis of Global WASH Cluster (GWC) documentation, and key informant interviews to summarise the outcomes and impacts of GWC coordination. Across these three datasets, consistent themes were identified, including: the cluster approach evol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 20 publications
(17 reference statements)
1
11
0
Order By: Relevance
“…On the other hand, the theory has limitations arising from the complexity that is synonymous with relief operations. For instance, it is challenging to manage and satisfy the ever-changing needs of all the multi-dimensional stakeholders more especially during a pandemic (Yates et al, 2020). That limits the application of the theory in some operations as was the case during the COVID-19 relief operations in 2020 in Uganda.…”
Section: Literature and Theoretical Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, the theory has limitations arising from the complexity that is synonymous with relief operations. For instance, it is challenging to manage and satisfy the ever-changing needs of all the multi-dimensional stakeholders more especially during a pandemic (Yates et al, 2020). That limits the application of the theory in some operations as was the case during the COVID-19 relief operations in 2020 in Uganda.…”
Section: Literature and Theoretical Reviewmentioning
confidence: 99%
“…That limits the application of the theory in some operations as was the case during the COVID-19 relief operations in 2020 in Uganda. The theory of change has in the recent past risen to prominence as many scholars are advocating for its use in designing and implementing relief operations interventions (Yates et al, 2020). Despite its apparent growth in usage, its proponents have registered varied results.…”
Section: Literature and Theoretical Reviewmentioning
confidence: 99%
“…Several pieces of research have indicated that measures for providing basic health services, including provision of adequate water, sanitation, and hygiene (WASH), are essential components in emergency crisis settings [ 28 , 29 ]. The WASH platform serves to prevent infectious diseases and their spread and sustain the dignity of vulnerable, displaced populations.…”
Section: Introductionmentioning
confidence: 99%
“…As there was a need to document results from the Cluster approach, previous research summarized the outcomes and impacts of WASH coordination in humanitarian response by collating information from the literature, UNICEF documents, and key informant interviews [8]. Overall, consistent themes were identified, including: the Cluster approach evolved into a costeffective 'best-fit' model; NCP staffs require technical and coordination skills; context is related to Cluster performance; and, there are trade-offs of Cluster participation for partners.…”
Section: Introductionmentioning
confidence: 99%
“…The goal of this research is to strengthen the previously developed Theory of Change [8] that will be used to improve global NCP strategies and, ultimately, intend to benefit affected populations. More specifically, this study aims to add NCP staff and partners feedbacks into the Theory of Change by gathering information from different humanitarian and WASH coordination contexts on the activities (inputs), outputs, outcomes, and impacts of humanitarian WASH coordination.…”
Section: Introductionmentioning
confidence: 99%